Effect of Coal Dust on Mucin Production by the Rat Trachea - V. P. Bhavanandan (The National Institute for Occupational Safety and Health (NIOSH), 1988)
The mucus secreted in the respiratory tract provides the first barrier against inhaled particulate and gaseous toxicants. Trachea removed from pathogen-free rats were maintained as organ cultures and used to study the effects of coal dust exposure on the synthesis of mucin. The high molecular weight isotopically labeled (3H-glucosamine, 14Cleucine or 35S-sulfate) mucin could be purified by gel filtration, treatment with testicular hyaluronidase, ion exchange chromatography, delipidation and CsBr density gradient centrifugation. To examine effect of coal dust on mucin production, groups of explant cultures were exposed to media containing coal dust at 100 µg per ml every 2 days for 2 weeks while control cultures were treated with media without dust. Analysis of the spent culture media showed that treatment with dust markedly decreased the production of nondialysable glycoproteins as well as hyaluronidase-resistant acid-precipitable fraction consisting mainly of mucin. Since the synthesis of protein was not affected to the same extent the decrease in mucin production is not entirely due to cell death. In separate experiments rats were subjected to in vivo coal dust exposure in inhalation chambers and tracheae of these and control rats were removed for explant cultures. The incorporation of precursor isotopes into mucin by these explant cultures are being examined. (Supported by U.S. Bureau of Mines through the Generic Mineral Technology Center for Respirable Dust under grant G1135142, project 4210).